Digital Capabilities ICT Adoption in Marginalized Communities in Israel and the West Bank - Schejter, Amit.; Shomron, Baruch; Abu Jafar, Muhammad; Abu Kaf, Ghalia; Mendels, Jonathan; Mola, Shula; Shacham, Malka; Al Sharha, Amneh; Tirosh, Noam. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
Digital Capabilities is a first-of-its-kind exploration of the capabilities that communities in positions of inequality in Israel and the West Bank seek to realize by utilizing information and communication technologies (ICT), the opportunities they have to communicate, and the way ICTs serve their desire to do so. It is the outcome of an eight-year research project in which the nine authors of this book, some of whom came from within the studied communities, conducted their work among the studied populations over an extended period of time. The capabilities approach, much discussed theoretically, takes on a life in this project and is presented as an empirically observable phenomenon for assessing whether ICTs are serving actual needs, whether communication resources are justly allocated and distributed and whether they serve the goal of a universally accessible right to communicate.
Part I: Foundations -- 1. The theoretical framework: The capabilities approach and social justice -- 2. The context: Marginalized communities in Israel and the West Bank -- Part II: Media and Technology -- 3. Mass media: The case of Israeli broadcast media and Arab-Israelis -- 4. Journalism: The case of Bedouin journalists -- 5. Digital role-playing games: The case of Arab-Israeli teachers -- 6. Mobile digital applications: The case of iNakba, voice and memory -- 7. Social networking applications: The case of Facebook and West Bank Palestinian activists -- Part III: Communities -- 8. Bedouin villagers in the Negev -- 9. Ultra-Orthodox Haredi women -- 10. Zera Beta Israel immigrant activists in absorption centers -- 11. The Bnei Menashe immigrant community -- 12. Asylum seekers and refugees -- 13. Conclusion: Policies and strategies towards a fair digital media society. .
Keywords: Digital media; Internet -- Social aspects; Mass media -- Political aspects; Digital and New Media; Internet Studies; Media Policy and Politics